A Bottleneck Analysis of Care and Feeding of the Small and Sick Newborn in Malawi: Findings and Proposed Solutions (P11-100-19). (13th June 2019) - Welch, Patricia; Kavle, Justine; Bwanali, Florence; Nyambo, Kanji; Khadka, Neena
Abstract: Objectives: The objectives of this bottleneck analysis are to 1) Diagnose bottlenecks at the health facility and health system levels in the provision of care and feeding of the small and sick newborn (SSNB) within the context of the Baby Friendly Hospital Initiative (BFHI) in Malawi, 2) Provide recommendations to address the identified bottlenecks. Methods: The Every Newborn Action Plan (ENAP) bottleneck analysis tool was adapted to provide an increased focus on care and feeding of the SSNB. Using the adapted bottleneck analysis tool, we conducted facility-based observations and interviews with clinical and supervisory staff at eight hospitals to assess for bottlenecks at the facility level. To identify health system bottlenecks, interviews were conducted with key district- and national-level Ministry of Health personnel, and a desk review of key national nutrition and child health policies and guidelines was conducted. Information collected from interviews and extracted from national policies and guidelines were collated and analyzed for the presence/absence of significant bottlenecks. Results: Significant bottlenecks were similar across the eight hospitals and included: unskilled staff in feeding concerns of the SSNB; overburdened and understaffed hospitals; lack of feeding cups for infants who are unable to suckle; limited space in the maternity ward for mothers and other caregivers to be present and feed their infant; no job aids or supportive supervision protocols or guidelines around care of the SSNB; no national policies in place to ensure monitoring of care of the SSNB. Key actions to address the identified bottlenecks are presented — including task shifting, improving mechanisms for monitoring care of SSNBs, and capacity-building of health providers — with consideration around how they could be implemented through Malawi's existing and scaled Baby-Friendly Hospital Initiative platform. Conclusions: This assessment revealed the need to strengthen the provision of care and feeding of the SSNB. Addressing gaps in each of the six ENAP building blocks will be critical for improving newborn nutrition and health outcomes, and Malawi's already existing BFHI platform could provide an ideal platform for addressing the identified bottlenecks. Funding Sources: United States Agency for International Development (USAID).